Perception, attitude, and practice of labor analgesia among obstetric care providers in Eastern Uttar Pradesh - Khan, Imran Ahmed; Aditya, Vani; Arun Kumar Srivastava; DK Srivastava (Asian Journal of Medical Sciences, 2023)
Background: Labor pain is among the foremost severe pain that ladies experience in their lifespan, if inadequately treated can lead to certain complications in labor. Relieving this pain with medical interventions is also full of misconceptions and disagreement among people. Different traditional and pharmacological methods for labor pain relief are utilized by obstetric care providers. Aims and Objectives: The aim of the study was to obtain perception, attitude, and practice of labor analgesia among obstetric care providers in Eastern Uttar Pradesh. Materials and Methods: A cross-sectional online survey was conducted among obstetric care providers practicing in eastern Uttar Pradesh to access the perception, attitude, and practice of labor analgesia. Results: A total of 152 valid responses were obtained from the 250 participants contacted (response rate of 60.8%). The majority (98%) of them were in favor of utilizing some or the other technique of labor pain relief, and 80.3% of the participants were utilizing some of the available methods solely or in combination. Non-pharmacological methods were the most frequently used technique (77.9%). Epidural analgesia was used by only 9.8% of participants. Less awareness among pregnant women, fear of harm to the baby, lack of dedicated supporting staff, and non-availability of anesthesiologists were among the most commonly pointed out as barriers to utilizing labor epidural analgesia. Conclusion: The majority of obstetric care providers were in favor of using some or the other technique of labor analgesia, but there was a large gap between the practice and attitude among health-care service providers regarding labor analgesia. Epidural analgesia was practiced very less due to some myths and scarcity of workforce.